Clinical applications of antineutrophil cytoplasmic antibody testing - Schmitt, Wilhelm; Woude, Fokko J. van der (Current opinion in rheumatology, 2004)
Purpose of review: Antineutrophil cytoplasmic antibodies are closely associated with Wegener granulomatosis, microscopic polyangiitis, and Churg-Strauss syndrome and have contributed to new pathogenetic concepts and improved nomenclature of systemic vasculitides (antineutrophil cytoplasmic antibody-associated vasculitides). However, the application of antineutrophil cytoplasmic antibody testing as a clinical diagnostic tool is still regarded as controversial. This review summarizes the most recent developments in the field, identifies areas of uncertainty, and gives practical guidelines. Recent findings: The problems of antineutrophil cytoplasmic antibody testing include the diversity of antineutrophil cytoplasmic antibody target antigens, assay standardization and performance, the application of antineutrophil cytoplasmic antibody testing in a clinical setting with a low pretest probability, and, finally, the widespread assumption that antineutrophil cytoplasmic antibody titers alone may closely reflect disease activity and therefore may be used to guide therapy. Summary: Recent findings demonstrate that the combined use of indirect immunofluorescence tests and solid phase assays to detect antineutrophil cytoplasmic antibody directed against myeloperoxidase and proteinase 3 can minimize the occurrence of false-positive antineutrophil cytoplasmic antibody results. Furthermore, the yield of antineutrophil cytoplasmic antibody testing can be improved by the use of a well-standardized test, adherence to published guidelines, and restricting the use of the tests to clinical situations with a rather high pretest probability for antineutrophil cytoplasmic antibody-associated vasculitides. However, treatment decisions should be based on the clinical presentation of the patient and histologic findings and not on the results of antineutrophil cytoplasmic antibody testing alone.
Gesehen am 02.06.2022